Renewable : the world-changing power of alternative energy - Shere, Jeremy (New York : St. Martin's Press, 2013)
An entertaining and informative guide to where renewable energy has been, where it is today, and where it's heading.
Includes index.
Keywords: Shere, Jeremy -- Travel -- United States; Renewable energy sources -- United States; Energy policy -- United States; Social change -- United States; Renewable energy sources -- History